2022
DOI: 10.1111/jfpp.16303
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of sweeteners from Stevia rebaudiana by semicontinuous percolation of untreated leaves and leaves pretreated with ethanol

Abstract: Stevia rebaudiana is a shrub of the Asteraceae family, native to South America. Sweeteners called steviol glycosides are extracted from the leaves of this plant, which have a sweetening power that can be up to 450 times greater than the sweetening power of sucrose (Das et al., 2015). Among the glycosides found in Stevia are stevioside, steviolbioside, rebaudiosides A, B, C, D, E, F and dulcoside (Ahmed & Mukta, 2017), being rebaudioside A, among the major glycosides, the one with the best sensory profile. NEPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, data from our research group, using the same variety of pre‐treated Stevia UEM‐13, show conventional aqueous extractions at high temperatures with yields around 40% (Formigoni et al, 2018) and yield of 41% with ultrasound‐assisted extraction (Raspe et al, 2021). Ciotta et al (2022), using the same semi‐continuous percolation extraction process, showed a yield of 41% using boiling water. Data that corroborate with the result found in this study.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, data from our research group, using the same variety of pre‐treated Stevia UEM‐13, show conventional aqueous extractions at high temperatures with yields around 40% (Formigoni et al, 2018) and yield of 41% with ultrasound‐assisted extraction (Raspe et al, 2021). Ciotta et al (2022), using the same semi‐continuous percolation extraction process, showed a yield of 41% using boiling water. Data that corroborate with the result found in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The FE presented 7.3% TPC and 25.3% sweeteners, being 10.2% stevioside, 11.9% rebaudioside A, and 3.2% rebaudioside C. The ME had 4.0% phenolic compounds and 8.1% total sweeteners, being 3.5% stevioside, 3.5% rebaudioside A, and 1.2% rebaudioside C. Raspe et al (2021) obtained 26 g/100 g of total sweeteners in the aqueous extract obtained by ultrasound‐assisted extraction. Ciotta et al (2022), using semi‐continuous extraction (100°C) of pre‐treated UEM‐13 leaves, obtained in the aqueous extract 31.56 g/100 of total glycosides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation